(untitled) (Journal of the College of Languages (JCL), 2024)
Patterns of utterance stress in discourse direct attention to specific themes and reactions, controlling the flow and coherence of conversation. this study examines the utterance stress in Steve Harvey’s selected episodes from a phono-stylistic perspective. this study is hoped to improve understanding of linguistic mechanism in talk show communication, highlighting the importance of phonetic features in transmitting meaning and increasing broadcast conversation participation. the researcher concentrates on the types of focus functions of utterance stress of some episodes available on YouTube. to conduct the analysis, the researcher adopts (Carr, 2013; Davenport& Hannahs 2005) to analyze utterance stress and Leech and Short (2007) to examine the stylistic features of the data selected. based on the adopted model, the study concludes: the study utilizes utterance stress, focus and content. while stylistic features include syntax, vocabulary, narrative viewpoint, politeness, impoliteness and cultural references.